A new species of Caipirasuchus (Notosuchia, Sphagesauridae) from the Late Cretaceous of Brazil and the evolutionary history of Sphagesauria. (16th February 2021) - Ruiz, Juan V.; Bronzati, Mario; Ferreira, Gabriel S.; Martins, Kawan C.; Queiroz, Marcos V.; Langer, Max C.; Montefeltro, Felipe C.
Abstract : Sphagesauridae is a group of notosuchian crocodyliforms from the Late Cretaceous of South America characterized by highly specialized jaws and dentition. Here, we describe a new sphagesaurid from the Santo Anastácio Formation (Caiuá Group, Bauru Basin), south-east Brazil. The specimen is composed of a partial palate, neurocranium, mandible and fragmentary teeth. It represents a new species that can be assigned to Caipirasuchus due to the presence of a lateromedially narrow and anteroposteriorly long mandibular symphyseal region, apicobasal ridges on the posterior teeth, a diastema between D5 and D6, and a linear row of large neurovascular foramina on the lateral surface of the dentary. It differs from previously described Caipirasuchus species based on a ventrolaterally inclined surface of the dentaries posterior to the tooth row, a connection between the anteroventral margin of the external mandibular fenestra and the floor of the Meckelian canal, and the anterior process of the angular forming a 'V'-shaped suture in its contact with the splenial. The results of a phylogenetic analysis of notosuchians recovered the so-called 'advanced notosuchians' in a clade, for which we propose a phylogenetic definition and erect the name Sphagesauria. We also recovered two more inclusive clades encompassing an array of Mesozoic notosuchians, here named Xenodontosuchia, which includes Sphagesauria + Baurusuchia, and Eunotosuchia, including Xenodontosuchia, Uruguaysuchidae and other Cretaceous forms. http://zoobank.org/urn:lsid:zoobank.org:pub:FD8D706F-9E01-4C09-BE4E-DC3BEDE151DC